Adiponectin and Orexin-A as a Potential Immunity Link Between Adipose Tissue and Central Nervous System - Polito, Rita; Nigro, Ersilia; Messina, Antonietta; Monaco, Maria L.; Monda, Vincenzo; Scudiero, Olga; Cibelli, Giuseppe; Valenzano, Anna; Picciocchi, Elisabetta; Zammit, Christian; Pisanelli, Daniela; Monda, Marcellino; et al. (Frontiers in Physiology, 2018)
Adipose tissue (AT) is strongly associated with development and progression of immune disorders through adipokines secretion, such as adiponectin. This protein has beneficial energetic properties and is involved in inflammation and immunity processes. Three oligomers of circulating Adiponectin with different molecular weight are described: High (HMW), Medium (MMW) and Low (LMW). The HMW is the most biologically active oligomers. On binding to its receptors AdipoR1, AdipoR2, and T-cadherin, adiponectin acts on both innate and acquired immunity. The suppression of NF-kB activation and pro-inflammatory cytokine expression in macrophages is mediated by AdipoR1. AdipoR2 mediates polarization of anti-inflammatory M2 macrophages T-cadherin is essential for the M2 macrophage proliferation. Furthermore, adiponectin reduces T-cells responsiveness and B-cells lymphopoiesis. The immune system is very sensitive to environmental changes and it is not only interconnected with AT but also with the central nervous system (CNS). Cytokines, which are mediators of the immune system, exercise control over mediators of the CNS. Microglia, which are immunity cells belonging to the macrophage family, are present within the CNS. The nervous system is also involved in immunity through the production of neuropeptides such as orexin-A/hypocretin-1. This neuropeptide is involved in metabolic disorders, inflammation and in the immune response. The relationship between adipokines, immunity and the nervous system, is validated by both the role of orexin-A on fat, food intake and energy expenditure, as well as by role of adiponectin on the central nervous system. In this review, we focused on the functions of adiponectin and orexin-A as a potential immunity link between AT and CNS.